2021
DOI: 10.1002/ijgo.13591
|View full text |Cite
|
Sign up to set email alerts
|

The role of sarcopenic obesity in high‐grade endometrial cancer

Abstract: Objective To investigate the relationship between obesity and sarcopenia in relation to overall survival (OS) and disease‐specific survival (DSS) in high‐grade endometrial cancer patients. Methods We conducted a retrospective study in women diagnosed with high‐grade endometrial cancer (EC) between February 2006 and August 2017 in the Royal Cornwall Hospital who had abdominal computerized tomography (CT)‐scan as part of routine staging work‐up. Sarcopenia was assessed by measuring psoas‐, paraspinal‐ and abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…While the nutritional status and sarcopenia has been described to have an impact on survival in endometrial cancer [44], this could not be confirmed for the BMI in our cohort of uterine sarcoma. Since the absolute value of a single marker does not always give an indication of the prognosis, we further applied the Nutritional Index that had been previously described to go along with inferior oncologic outcomes in gastrointestinal and lung cancer [27], but neither a prediction of OS nor LC or DC was found.…”
Section: Discussioncontrasting
confidence: 79%
“…While the nutritional status and sarcopenia has been described to have an impact on survival in endometrial cancer [44], this could not be confirmed for the BMI in our cohort of uterine sarcoma. Since the absolute value of a single marker does not always give an indication of the prognosis, we further applied the Nutritional Index that had been previously described to go along with inferior oncologic outcomes in gastrointestinal and lung cancer [27], but neither a prediction of OS nor LC or DC was found.…”
Section: Discussioncontrasting
confidence: 79%
“…The selection of a muscle for determining the sarcopenia index is very important [21]. Although ideally sarcopenia would be measured in the whole skeletal muscle, in practice this would be too complicated for a clinical setting, because it would require additional software packages, and the Hans eld is very different among patients [16,23,25]. In this study, we selected the psoas, iliac, and paraspinal muscles for calculating the sarcopenia index [22].…”
Section: Discussionmentioning
confidence: 99%